Homocysteine and thyroid diseases - Lili Cui; Fei Wang; Chunyu Li; Fan Liu; Haipeng Wang; Junyu Zhao (Frontiers in Endocrinology)
Homocysteine (Hcy) is an important intermediate product in methionine metabolism which plays a key role in the methylation of DNA, RNA and proteins. High level of Hcy can induce endothelial cell damage, promote the release of inflammatory factors, stimulate oxidative stress and inhibit the fibrinolytic system. Numerous studies have confirmed the close relationship between hyperhomocysteinemia (HHcy) and the occurrence/development of various diseases such as cardiovascular diseases, neurological disorders, thrombotic diseases, and tumors. With the rising incidence of thyroid diseases, the relationship between Hcy and thyroid diseases has attracted widespread attention. It has been found that HHcy may be directly or indirectly associated with the development of hypothyroidism, but the findings with hyperthyroidism, chronic lymphocytic thyroiditis and reduced thyroid hormone sensitivity are controversial. This article reviews the research progress of Hcy and thyroid diseases, with a view to providing new ideas for the prevention and clinical treatment of diseases.